Women's Lyric Poetry in Algeria: The Hawfi of Tlemcen - Nebia DADOUA HADRIA (Turath)
The Just as men compose popu-lar poetry or malhoun on various occasions, women also express their emotions throughout different moments of their daily lives, often while engaged in household tasks. During a period in Algeria’s history marked by a rich tradition of arts and vernacular poetry, the women of Tlemcen distinguished themselves through creative poetic expression, producing a lyrical form that still bears the cultural and linguistic imprint of the region. This article aims to redefine this poetic genre by drawing on previous scholarly work. We have also chosen to broaden the scope of our analysis by presenting examples of women's poetry from other Arab countries, before focusing more specifically on the hawfi tradition of Tlemcen.